THE LOCAL CONSTRUCTION OF RELIGIOUS BLASPHEMY IN EAST JAVA (JOURNAL OF INDONESIAN ISLAM, 2019)
The blasphemy case of Basuki Tjahaja Purnama, known as Ahok, who is a Christian and was Jakarta’s non-Muslim governor, has sparked different reactions among Muslim groups in Indonesia. Reactions of Muslim groups of different persuasion in East Java will be highlighted in this article. Two theological constructions emerged out of this case, namely textual-normative and moderate-substantive constructions. This article aims to identify theological construction and social actions as normative propositions and actions of Muslim groups in East Java. To comprehend the concepts and responses through the article, several leaders of the Muslim roups such as FPI (Front Pembela Islam), HTI (Hizb al-Tahrir Indonesia), FUI (Forum Umat Islam), MMI (Majlis Mujahidin Indonesia), Al-Irsyad, FS-LDK (Forum Studi Lembaga Dakwah Kampus), NU (Nahdlatul Ulama) and Muhammadiyah were interviewed. The article finds that moderate and rational theological concept of blasphemy is coined by major Muslim groups especially NU and Muhammadiyah which prioritize greater national interest, whereas other Muslim roups, especially those with literal interpretation, promote political identity vis-à-vis other religious groups.